Recycling method of material of waste lithium iron phosphate battery - ZHANG ZHEMING; WU ZHENGBIN; YANG FANG (2018)
The invention provides a recycling method of a material of a waste lithium iron phosphate battery. Lithium iron phosphate on a positive electrode plate of the waste lithium iron phosphate battery is taken as the raw material; and lithium iron phosphate is separated from the positive electrode plate of the battery by adopting an ultrasonic cleaning method, and redundant Li+, Fe<2+> and PO <3-> are removed from lithium iron phosphate so as to obtain a regenerative lithium iron phosphate material. The method is simple and easy to operate, capable of improving recovery rate, relatively low in energy consumption, environment-friendly, and does not generate secondary pollutants. 本发明提供的废旧磷酸铁锂电池的材料回收利用方法，以废磷酸铁锂电池正极片上磷酸铁锂为原料，采用超声清洗的方法使磷酸铁锂从电池正极片上分离，并除去磷酸铁锂中多余的中Li、Fe和PO，从而获得再生的磷酸铁锂材料，上述方法简单易于操作，提高了回收率，能耗较低，对环境友好，不产生二次污染物。